Implementing a community-based task-shifting psychosocial intervention for individuals with psychosis in Chile: Perspectives from users. (February 2019) - Agrest, Martin; Le, PhuongThao D; Yang, Lawrence H; Mascayano, Franco; Alves-Nishioka, Silvia; Dev, Saloni; Kankan, Tanvi; Tapia-Muñoz, Thamara; Sawyer, Samantha; Toso-Salman, Josefina; Dishy, Gabriella A; Jorquera, Maria Jose; et al.
Background: Latin America, and Chile in particular, has a rich tradition of community mental health services and programs. However, in vivo community-based psychosocial interventions, especially those with a recovery-oriented approach, remain scarce in the region. Between 2014 and 2015, a Critical Time Intervention-Task Shifting project (CTI-TS) was implemented in Santiago, Chile, as part of a larger pilot randomized control trial. CTI is a time-limited intervention delivered at a critical-time to users, is organized by phases, focuses on specific objectives and decreases in intensity over time. CTI-TS, which combines both the task-shifting strategy and the use of peers, introduces a novel approach to community mental health care that has not yet been tried in Chile. Aims: We aim to evaluate the feasibility, acceptability and applicability of such a community-based psychosocial intervention in urban settings in Latin America – specifically, in Santiago (Chile) from a user perspective. Method: We analyzed 15 in-depth interviews ( n  = 15) with service users who participated in the intervention about their perceptions and experiences with CTI-TS through thematic analysis. Results: Three themes were revealed. The first was related to the structural characteristics of CTI-TS, especially regarding the timing, duration and phasic nature of the intervention. The second pertained to the acceptability of the in vivo community-based approach. The third theme dealt with the task-shifting aspect, that is, users' perceptions of the peer support workers and the community mental health workers. Conclusions: CTI-TS was generally acceptable in this Latin American context. Users' perspectives pointed to the need to make adjustments to some of the structural characteristics of the CTI model and to combine this type of intervention with others that can address stigma. Thus, future adaptations of CTI-TS or similar psychosocial interventions in Latin American contexts are feasible and can enhance community mental health in the region.